Presentation of Ma'badong Music in the Context of Social Action in Lembang Gandangbatu - Sambira, Zefanya; Wadiyo, Wadiyo; Syakir, Syakir (Catharsis, 2020)
Ma'badong music is a music that is presented in the Ma'badong performance at the Rambu Solo' ritual or death ritual in Lembang Gandangbatu, Gandangbatu Sillanan District, Tana Toraja Regency as an expression and lamentation for someone who has died. This study uses qualitative research method with a sociological approach. The data analysis used to analyze the presentation of Ma'badong music in the context of social action consists of three stages, namely: data reduction, data presentation, and drawing conclusions. The data collection techniques used were observation, interview, and documentation techniques. The results suggest that the presentation of Ma'badong music in Lembang Gandangbatu consists of four types of social action proposed by Max Weber, namely: objective rational action, value rational action, affective action, and traditional action. Pa'badong acts as an actor or music presenter of Ma'badong that tried to present their best performance through melodies, rhythms, and lyrics in Badong which are full of meaning and noble values upheld by the Toraja tribe. Meanwhile, individuals or groups of people who watch Ma'badong performance act as appreciators or audience. The presentation of Ma'badong music is not only seen as part of religious rituals and performing arts, but also as a form of social action that occurs in Tana Toraja community, especially in Lembang Gandangbatu. Ma'badong music is a music that is presented in the Ma'badong performance at the Rambu Solo' ritual or death ritual in Lembang Gandangbatu, Gandangbatu Sillanan District, Tana Toraja Regency as an expression and lamentation for someone who has died. This study uses qualitative research method with a sociological approach. The data analysis used to analyze the presentation of Ma'badong music in the context of social action consists of three stages, namely: data reduction, data presentation, and drawing conclusions. The data collection techniques used were observation, interview, and documentation techniques. The results suggest that the presentation of Ma'badong music in Lembang Gandangbatu consists of four types of social action proposed by Max Weber, namely: objective rational action, value rational action, affective action, and traditional action. Pa'badong acts as an actor or music presenter of Ma'badong that tried to present their best performance through melodies, rhythms, and lyrics in Badong which are full of meaning and noble values ​​upheld by the Toraja tribe. Meanwhile, individuals or groups of people who watch Ma'badong performance act as appreciators or audience. The presentation of Ma'badong music is not only seen as part of religious rituals and performing arts, but also as a form of social action that occurs in Tana Toraja community, especially in Lembang Gandangbatu.